Programa de producción más limpia en la empresa artesanal de confecciones deportivas Casa Deportiva Lucho Quishpi - Salto Morquecho, Mariela Elizabeth
In these present chapters are about to the Artisan Confections Factory CASA DEPORTIVA LUCHO QUSHPI W. Its strategic plan detailing the activities to develop each subsystem, the resources involved in the production and also, what are their suppliers, what are the customers and its main products it generates by this company. It also shows some terms relating to the application of Cleaner Production. It is a diagnosis of the current situation in the areas of cortado-cosidoandserigrafía, and identifies the causes what start wastes which are generated in their processes and production activities as well as bad practices leading to operational excessive power consumption. I am going measurements of wastes in is performed in a quality of clothing and assesses the economic losses that are of great importance for the company, and this poses the Design of a CLEANER PRODUCTION PROGRAMME, which provides measures and tools to optimize the resources in production. The implementation of this program will provide great benefits both business and environmental